Assessing social welfare department service delivery system towards vulnerable and disadvantages group in Malaysia: case study of Perak - Mohamed Osman, Mariana; M Bakri, Nurul Izzati; Bachok, Syahriah; Ibrahim, Mansor; Mohamed, Mohd Zin (Elsevier, 2015)
This paper attempted at evaluating the services delivery of the Welfare Department in Perak, Malaysia offered to the vulnerable groups in achieving good governance and social sustainability. Improving the quality of government delivery system is challenging, but effective delivery systems were crucial in achieving the people’s satisfaction level. This study applied a face to face semi-structured questionnaire survey to 250 respondents from varies category of vulnerable and disadvantaged group within Perak. This research identified there was a relationship between service delivery system performed by government agencies and the quality of life of the respondents, in the context of social sustainability for human security. The findings from this research offer several recommendations for improving the government delivery system in Perak.